2018
DOI: 10.1002/admt.201800238
|View full text |Cite
|
Sign up to set email alerts
|

Cycling‐Induced Degradation of Organic–Inorganic Perovskite‐Based Resistive Switching Memory

Abstract: As one key issue of resistive switching (RS) memory, the cycling endurance is poorly understood in hybrid perovskite‐based memory devices. Here, the cycling failure and the corresponding cycling‐induced degradation of CH3NH3PbI3‐based resistive random access memory devices are discussed. The high resistance state clearly decreases with the number of operation cycles, finally triggering irreversible failure in the collapse of switching window. By monitoring the I–V curves for all cycles, a negative set event is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…The write‐read‐erase‐read sequence test was conducted to demonstrate the switching characteristic of the perovskite memory device . The applied voltage pulse cycle was designed as shown in the top panel of Figure b: 2 V to write (Set), 0.2 V to read out the current ( I LRS ), −2 V to erase (Reset), and 0.2 V to read out I HRS ; the duration of each pulse is 1 s. The current response for applied voltage pulse cycles is shown in the lower panel of Figure b.…”
mentioning
confidence: 99%
“…The write‐read‐erase‐read sequence test was conducted to demonstrate the switching characteristic of the perovskite memory device . The applied voltage pulse cycle was designed as shown in the top panel of Figure b: 2 V to write (Set), 0.2 V to read out the current ( I LRS ), −2 V to erase (Reset), and 0.2 V to read out I HRS ; the duration of each pulse is 1 s. The current response for applied voltage pulse cycles is shown in the lower panel of Figure b.…”
mentioning
confidence: 99%
“…Xu et al addressed the cycling-induced degradation of a Al/MAPbI 3 /FTO memristor. 130 They observed an anomalous RESET behavior (which was termed as negative SET) in the I-V curve of the 60th cycle and the HRS degenerated at 258th cycle (see Figure 15A). The filamentary memristive mechanism of the memristor was verified with conductive-AFM (c-AFM) measurement ( Figure 15C).…”
Section: Memristive Characteristics For Memory Applicationsmentioning
confidence: 99%
“…Up to now, few reports are available on the endurance characteristics of OHP‐based memristors and the cycling endurance degradation mechanism is poorly understood. Xu et al addressed the cycling‐induced degradation of a Al/MAPbI 3 /FTO memristor . They observed an anomalous RESET behavior (which was termed as negative SET) in the I‐V curve of the 60th cycle and the HRS degenerated at 258th cycle (see Figure A).…”
Section: Memristors Based On Ohpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we pay our attention to recent progress in OIP‐based resistive switching memories 37,52,58,215‐225 . Previous studies have revealed that two mechanisms, ionic migration and charge trapping/detrapping, can account for the resistive switching behaviors of OIPs, 218,219 which guided a series of materials design. In 2015, Yoo et al claimed for the first time the successful fabrication of an OIP‐based memristor, which possessed fascinating nonvolatile memory properties 220 .…”
Section: Organic‐inorganic Hybrid Materials For Resistive Memorymentioning
confidence: 99%